Physical, Chemical, and Biological Pollution in Water, Air and Soil Industrial Products From PT. Torabika Eka Universe in Cikupa Tangerang - Mona Gusfira; Fatmawati Fatmawati; Dedi Agustanto; Lismomon Nata; Frinsis Warmansyah; Eri Barlian; Indang Dewata; Iswandi Umar; Nurhasan Syah; Siti Fatimah; Indra Catri (Postgraduate School, Universitas Negeri Padang, 2023)
Technological developments certainly provide big changes in human life, starting from infrastructure management to the food industry, and the drug industry, everything is very easy to do by utilizing current technological sophistication. Many bad impacts arise from these technological advances, the most prominent of which is pollution due to waste generated from the industry. The impact that occurs from failure in waste treatment is the occurrence of air, soil, and water pollution. This research method is a qualitative descriptive research, where the researcher directly becomes the instrument and the company is the respondent. Based on research results Pollution of water, air, and soil due to the industrial products of PT. Torabika Eka Semesta found that Torabika is a well-known coffee drink brand in Indonesia. To maintain a healthy environment, the Torabika company can do several things, including 1) Companies reduce their use of single-use plastic packaging; 2) Use environmentally friendly raw materials; 3) Optimizing energy use; 4) Improve recycling programs; 5) Build environmental awareness among employees and customers; 6) Improve recycling programs; 7) Build environmental awareness among employees and customers; 8) Improve recycling programs; and 9) Build environmental awareness among employees and customers.